Randomised trial of proton vs. carbon ion radiation therapy in patients with chordoma of the skull base, clinical phase III study HIT-1-Study - Nikoghosyan, Anna; Karapanagiotou-Schenkel, Irini; Münter, Marc; Jensen, Alexandra; Combs, Stephanie; Debus, Jürgen (BMC cancer, 2010)
Chordomas of the skull base are relative rare lesions of the bones. Surgical resection is the primary treatment standard, though complete resection is nearly impossible due to close proximity to critical and hence also dose limiting organs for radiation therapy. Level of recurrence after surgery alone is comparatively high, so adjuvant radiation therapy is very important for the improvement of local control rates. Proton therapy is the gold standard in the treatment of skull base chordomas. However, high-LET beams such as carbon ions theoretically offer biologic advantages by enhanced biologic effectiveness in slow-growing tumors.
Gesehen am 17.05.2023